2016
DOI: 10.3892/ol.2016.4716
|View full text |Cite
|
Sign up to set email alerts
|

Psoralidin inhibits proliferation and enhances apoptosis of human esophageal carcinoma cells via NF-κB and PI3K/Akt signaling pathways

Abstract: Abstract. Esophageal cancer is the most common gastrointestinal cancer. Psoralidin exhibits antioxidant, anti-apoptotic, anti-inflammatory and antitumor effects, which result in the inhibition of cancer formation. The present study aimed to investigate the effect of psoralidin on esophageal carcinoma proliferation and growth, and to elucidate its underlying mechanism of action. The effect of psoralidin on cell proliferation was investigated using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium brom ide as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Therefore, we aimed to investigate whether PL could reverse excessive caffeine-caused injury in vitro and in vivo and, if so, to elucidate the underlying mechanisms. Documented studies have demonstrated that PL regulates several extracellular signaling pathways, which include the protein kinase B/glycogen synthase kinase 3β/β-catenin signaling pathway, the nuclear factor-kappa B (NF-κB) and phosphatidylinositol 3 kinase (PI3K)/Akt signaling pathway, and the NF-κB and B-cell lymphoma-2 (Bcl-2)/ Bcl-2 associated X protein (Bax) signaling pathway (16,29,30). Previous studies have demonstrated that PL can inhibit the formation of adipocytes by modulating the classical and membrane ER pathways (16).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we aimed to investigate whether PL could reverse excessive caffeine-caused injury in vitro and in vivo and, if so, to elucidate the underlying mechanisms. Documented studies have demonstrated that PL regulates several extracellular signaling pathways, which include the protein kinase B/glycogen synthase kinase 3β/β-catenin signaling pathway, the nuclear factor-kappa B (NF-κB) and phosphatidylinositol 3 kinase (PI3K)/Akt signaling pathway, and the NF-κB and B-cell lymphoma-2 (Bcl-2)/ Bcl-2 associated X protein (Bax) signaling pathway (16,29,30). Previous studies have demonstrated that PL can inhibit the formation of adipocytes by modulating the classical and membrane ER pathways (16).…”
Section: Discussionmentioning
confidence: 99%
“…PSO promotes cellular apoptosis and inhibits the cancer cells proliferation in prostate cancer (Szliszka et al, 2011;Das et al, 2014); breast cancer (Dwarampudi et al, 2012); liver cancer (Luo et al, 2013); colon cancer (Jin et al, 2016a); esophagal carcinoma (Jin et al, 2016b), or modulate the autophagy in the lung (Hao et al, 2014;Xin et al, 2019).…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…PSO significantly decreases cell proliferation and promotes apoptosis of Eca9706 cells in a dose-dependent manner. Moreover, it suppresses caspase-3 and NF-κB activities and also decreases the phosphatidylinositol-3-kinase (PI3K) and protein kinase B (Akt) protein expression dose-dependently (Jin et al, 2016b). Other in vitro studies on cell lines reported that PSO binds to both types of alpha and beta estrogen receptors, activating the classic estrogen receptor signaling pathway, thus explaining the effect of reducing bone loss as well as the antioxidant action (Liu et al, 2014).…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Psoralidin can also induce cells to produce reactive oxygen species (ROS), thereby inducing DNA damage and autophagy in breast cancer MCF-7 cells [18]. Jin et al [19] demonstrates that psoralidin can inhibit the proliferation and enhance apoptosis of human esophageal cancer cells by affecting NF-0202B and PI3K/Akt signaling pathways. Wang's study indicates that psoralidin has antioxidant activity and α-glucosidase inhibitory activity [20].…”
Section: Introductionmentioning
confidence: 99%